Customer’s adoption towards Islamic Banking among Non-Muslim a case study in Shah Alam, Selangor / Zul Hasanuddin Zulkefli - Zulkefli, Zul Hasanuddin (Bachelor Of Business Administration (Hons) Marketing, 2015)
The purpose of this study is to analyze the customer‟s adoption towards Islamic Banking among non-Muslim. This researcher has decided to choose 150 respondents which are area around Shah Alam as respondent for this study. The objective of this study are to identified the relationship between awareness, perception, and preferences with consumer adoption towards Islamic Banking. Besides that, this study is a quantitative research study whereby the findings of the study were analysed by using the Statistical Package for the Social Science (SPSS). Next, the data collected in this study is analyses by using Frequency, Descriptive analysis, Reliability test, Pearson‟s Correlation Coefficient and multiple Regressions in order to achieve the research objective. The objective for this research study is to identify the relationship between awareness, perception, and preferences with the adoption towards Islamic banking, Second, to analyse most significant factor on consumer‟s adoption toward Islamic banking among non-Muslim consumers in Malaysia. Based on this research study, the researcher found that this research have relationship between independent variables and dependent variable. Besides that, all hypothesis for this research also significant which is the relationship between independent variables and dependent variable. Lastly, the researcher found that the most significant factor on consumer‟s adoption towards Islamic Banking among non-Muslim. Awareness towards Islamic banking becomes the dominant predictor of independent variable since it has the highest Cronbach‟s alpha, Pearson‟s analysis, beta t-value and the lowest p-value among other independent variables